2017
DOI: 10.1001/jamadermatol.2016.6138
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Melanoma In Situ Treated With Mohs Micrographic Surgery Compared With Wide Local Excision

Abstract: IMPORTANCE Melanoma in situ (MIS) is increasing in incidence, and expert consensus opinion recommends surgical excision for therapeutic management. Currently, wide local excision (WLE) is the standard of care. However, Mohs micrographic surgery (MMS) is now used to treat a growing subset of individuals with MIS. During MMS, unlike WLE, the entire cutaneous surgical margin is evaluated intraoperatively for tumor cells.OBJECTIVE To assess the outcomes of patients with MIS treated with MMS compared with those tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 36 publications
(68 reference statements)
2
67
0
1
Order By: Relevance
“…Currently, no published clinical trials have examined the role of MMS vs. wide local excision (WLE) for melanoma, despite the fact that the use of MMS for melanoma is increasing in the U.S.A. 1 The limited retrospective data that does exist demonstrates MMS as an equally effective modality for the management of melanoma in situ, lentigo maligna melanoma, and cutaneous head and neck melanomas. 2,3 Currently, MMS is primarily used for in situ and very thin melanomas. Therefore, we sought to examine the role of MMS in localized melanomas, according to the American Joint Committee on Caner (AJCC) cancer staging manual (sixth and seventh editions).…”
Section: Conflicts Of Interest: None To Declarementioning
confidence: 99%
“…Currently, no published clinical trials have examined the role of MMS vs. wide local excision (WLE) for melanoma, despite the fact that the use of MMS for melanoma is increasing in the U.S.A. 1 The limited retrospective data that does exist demonstrates MMS as an equally effective modality for the management of melanoma in situ, lentigo maligna melanoma, and cutaneous head and neck melanomas. 2,3 Currently, MMS is primarily used for in situ and very thin melanomas. Therefore, we sought to examine the role of MMS in localized melanomas, according to the American Joint Committee on Caner (AJCC) cancer staging manual (sixth and seventh editions).…”
Section: Conflicts Of Interest: None To Declarementioning
confidence: 99%
“…However, accumulating evidence suggests that 5 mm margins may be inadequate as the tumor may extend beyond the visible pigmented lesion. The disadvantages of traditional Mohs micrographic surgery include the use of frozen sections, and one study found no significant difference in 5‐year recurrence rates between MIS treated with Mohs vs wide local excision …”
Section: Discussionmentioning
confidence: 99%
“…Given the necessity for increased margins in treating MIS, using a staged excisional technique such as the “slow Mohs” approach is advantageous since the entire margin is assessed. Therefore, physicians are able to discern exactly where additional excision of affected tissue needs to be performed, and it may lead to better cosmetic outcomes, which is important since the lentigo maligna subtype frequently occurs on the face . Scouting biopsies, which serve as a negative internal control, performed concurrently with surgical excision of MIS can be useful as a reference in comparing benign, sun‐damaged skin with equivocal margins to aid in determining if additional excisions should be taken.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study focused on invasive lesions, compared to MIS for the present study. Nosrati and colleagues performed a retrospective cohort study of 662 patients with MIS. There were 385 cases of WLE and 277 cases of MMS.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have directly compared WLE versus MMS techniques for the surgical management of MIS. Nosrati et al performed a retrospective study of 662 patients with MIS and did not find a significant difference in recurrence rates, overall survival, or melanoma‐specific survival between the two groups. Using a nationwide database, we sought to compare the survival outcomes of WLE versus MMS techniques for MIS.…”
Section: Introductionmentioning
confidence: 99%